EFFECT OF WORKLOAD, COMPENSATION, AND CLAN ORGANIZATION CULTURE ON NURSE TURNOVER INTENTION ANALYSIS AT SENTRA MEDIKA SANGGAU HOSPITAL - Windy Ratu Dewi; Erry Yudhya Mulyani; Rokiah Kusumapradja (Jurnal Cinta Nusantara (JCN), 2023)
Increased turnover of employees, particularly nursing staff, in healthcare institutions, especially hospitals, can reduce service quality and even result in losses. The best single predictor of employee turnover behavior is turnover intention. Employee turnover can be avoided by lowering the turnover intention. This study intends to investigate the effect of workload, compensation, and clan organization culture on turnover intentions. The study employed a quantitative approach as well as a questionnaire-based survey method. The population consists of the entire nursing staff at the Sentra Medika Sanggau Hospital. Total sampling is used in this study, with a total sample of 47 respondents. Multiple linear regression analysis is used in data analysis methods. The workload, compensation, and clan organization culture both simultaneously or partially have significant effects on the turnover intention of the nurses at Sentra Medika Sanggau Hospital. Implications for managers: migration of manual medical records to electronic medical records, enhancement of compensation, and enhancement of clan organization culture implementation